The Role of Service Value Agility for Student Entrepreneurship - Dika Vivi Widyanti; Jati Nugroho; Azizah, Azizah; Winarto, Winarto; Isnaini Nurkhayanti (Cita konsultindo, 2024)
The role of higher education in fostering entrepreneurship is increasingly recognized as vital for economic development and innovation. This study investigates the impact of Service Value Agility on student entrepreneurship within the D3 Marketing Management Study Program at the Department of Business Administration, Semarang State Polytechnic (Polines). By developing a conceptual framework that examines the relationships between market orientation, entrepreneurship knowledge, service value agility, product value customization, and entrepreneurial performance, this research employs structural equation modeling (SEM) to test these hypotheses. The results indicate that both market orientation and entrepreneurship knowledge significantly enhance service value agility and product value customization, which in turn positively influence entrepreneurial performance. The findings underscore the importance of integrating practical, market-oriented approaches into higher education curriculum to enhance service agility and entrepreneurial success among students. This study contributes to the literature on entrepreneurial education and offers valuable insights for educators and policymakers aiming to cultivate successful entrepreneurs.